Pengaruh E-WOM, Daya Tarik Wisata Dan Citra DestinasiTerhadap Minat Berkunjung (Studi Pada Destinasi Wisata Pemandian Telogo Sewu Pandaan) - Fauzarudin, Rifiyan; Hidayati, Nur; Khalikussabir, Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study was conducted to see the effect of Electronic Word of Mouth, Tourism Attraction and Destination Image on Visiting Interest in the Telogo Sewu Pandaan Bathing Destination. The population in this study were the people of Pandaan District with a sample size of 80 people, using sampling techniques, namely non-probability sampling techniques and purposive sampling methods. Multiple linear regression and hypothesis testing are used for the analysis method using Eviews 12 SV software. The results of the analysis obtained are the Electronic Word of Mouth and Tourism Attraction Variables have a significant influence on Visiting Interest. While the Destination Image Variable has an insignificant influence on Visiting Interest. Keywords : Tourist Destination, Electronic Word Of Mouth, Attractiveness Of Tourist Attractions, Destination Image.